"The one who controls the diamond wears the crown! The politicization of the Kimberley Process in Zimbabwe". (March 2016) - Munier, Nathan
Abstract: Why has Zimbabwe, a state that has been notorious for an utter disregard of international agreements, spent resources to implement policies that are in compliance with the Kimberley Process diamond certification scheme? In this research I explain variation in Zimbabwean regulatory policy in response to the Kimberley Process since 2003. This article contends that this variation can be best understood by tracing the political economy of factional rivalries within the ruling Zimbabwe African National Union – Patriotic Front (ZANU-PF) party. This research demonstrates that although the behavior of international regimes and private economic actors matter, in Zimbabwe it is government factions within ZANU-PF that are the main decision makers in relation to Kimberley Process regulations. This explains both why compliance with the Kimberley Process has been lower than other states in Southern Africa and why Zimbabwe has raised its level of compliance with the regulatory regime overtime. Highlights: Zimbabwe has had four different regulatory strategies in response to the Kimberley Process. Variation in regulatory policy is due to the political economy of factional rivalries. Kimberley Process regulations are used as a political instrument to gain market share.